Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Keterampilan Menulis Teks Resensi Siswa Kelas XI MAN 2 Kota Padang - Nurul Fitri; Atmazaki Atmazaki (Universitas Katolik Widya Karya Malang, 2023)
This study aims to describe the effect of using the jigsaw cooperative learning model on the writing skills of review texts of class XI MAN 2 Padang City students. This type of research is quantitative with experimental methods. The research design used was The Posttest Only Control Group Design. The study population was class XI MAN 2 Padang City using a purposive sampling technique for sampling. The selected sample consists of two classes, namely the experimental class and the control class. The data in this study were scores of students' review text writing skills in class XI MAN 2 Padang City using the jigsaw cooperative learning model and conventional learning models. The research instrument is a performance test. Based on the results of data management, it shows that the average value of students using the jigsaw cooperative learning model is 85.42 while the average value of students using the conventional method is 73.50. The results of the hypothesis test show that tcount > ttable (6.09 > 1.68). Thus, it shows that the jigsaw type cooperative learning model is better than using conventional methods.